2012
DOI: 10.1088/1674-1056/21/5/057501
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure, magnetism, and colossal magnetoresistance of Y 2 CrS 4

Abstract: The crystal structure, magnetism, and colossal magnetoresistance of Y 2 CrS * 4 Liu Rong-Deng(刘荣灯) a)b) , Liu Yun-Tao(刘蕴韬) a) , He Lun-Hua(何伦华) b) , Wang Zhi-Cui(王志翠) b) , Chen Dong-Feng(陈东风) a) , and Wang Fang-Wei(王芳卫) b) † a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…[ 59 ] The (111) polar orientation enhanced piezoelectric generation property is observed in CdO film with different (111) orientations. [ 60 ] In addition, the polar‐orientated Co 3 O 4 and PbTiO 3 films have been found to demonstrate enhanced piezoelectric generation and bulk photovoltaic properties and these studies are being continued. The results fully illustrate that the piezoelectric effect originates from the polar structure rather than the non‐centrosymmetric structure.…”
Section: Resultsmentioning
confidence: 99%
“…[ 59 ] The (111) polar orientation enhanced piezoelectric generation property is observed in CdO film with different (111) orientations. [ 60 ] In addition, the polar‐orientated Co 3 O 4 and PbTiO 3 films have been found to demonstrate enhanced piezoelectric generation and bulk photovoltaic properties and these studies are being continued. The results fully illustrate that the piezoelectric effect originates from the polar structure rather than the non‐centrosymmetric structure.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the formal precisions, the precision of the ionospheric slant delay estimates can be validated with the between-receiver (BR) differences of short or zero baselines (Ciraolo et al 2007, Liu et al 2017. The BR differences of STECs eliminate the lumped satellite DCBs and most of the ionospheric errors, with the BR RDCBs and the ionospheric delay residuals being the remaining parameters.…”
Section: Results Of the Ionosphere Vtec Modelingmentioning
confidence: 99%
“…Further, several recent studies have used the PPP approach with raw observations to retrieve ionospheric observables (Tu et al 2013, Zhang 2016, Liu et al 2017, Zhang et al 2017, Liu et al 2018. Although PPP relies on precise orbit/clock products and includes a more complicated data processing than that of the CCL method, the PPP-derived ionospheric slant delays are not affected by levelling errors (which might have undesired effects on ionosphere modeling) (Ciraolo et al 2007) and are more precise (Zhang 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The nano-composites have adsorbed arsenic following a pseudo-second-order kinetic model, which implied a chemical absorption mechanism. Comparably, Cheng Liu et al 100 showed a new magnetic chitosan nanoparticle (MCNP) performance to eliminate arsenic and its separation from water. 100 The study found that MCNP had a relatively short period and better efficiency in adsorption of arsenic, and the thermodynamic analysis showed the exothermic and spontaneous adsorption of As(III), and the data fitted well with the Langmuir isotherm model.…”
Section: Adsorptionmentioning
confidence: 99%
“…Comparably, Cheng Liu et al 100 showed a new magnetic chitosan nanoparticle (MCNP) performance to eliminate arsenic and its separation from water. 100 The study found that MCNP had a relatively short period and better efficiency in adsorption of arsenic, and the thermodynamic analysis showed the exothermic and spontaneous adsorption of As(III), and the data fitted well with the Langmuir isotherm model. The maximum adsorptions of 65.5 mg/g for As(V) and 60.2 mg/g for As(III) were measured at pH 6.8, which was relatively good compared to other granular adsorbents mentioned previously.…”
Section: Adsorptionmentioning
confidence: 99%